Vulnerability and the Climate Change Regime - Mboya, Atieno (eScholarship, University of California, 2018)
Climate change is precipitating social issues that are not traceable to a discreet, culpable actor. This is because greenhouse gas accumulation in the stratosphere is a global problem transcending the socio-political boundaries that law uses to assign responsibility. The diffuse nature of climate change calls for new legal approaches that can provide greater juridical responsiveness [1] to social problems and universal human vulnerability that is emerging in the wake of one of the most pressing environmental challenges facing the international community today. [2] Those social problems include displacement and dispossession of indigenous communities whose livelihoods depend directly on their environment, such as Arctic communities in Alaska, rural dwellers in the Himalayas, livestock farmers in the Kalahari, and forest-dwellers in the Amazon. [3] Farming communities reliant upon rain-fed agriculture also face food insecurity due to changing, unpredictable rainfall patterns. [4] While social impacts may be most keenly felt at the local level, the global nature of climate change means that jurisprudential bases of law at all levels—local, national, regional, and international [5] —need to promote coherent legal responses that recognize the global genesis of what may be seen as localized problems. This essay will draw on human vulnerability theory to discuss law’s role in promoting social justice in the wake of climate change. Vulnerability is the “characteristic that positions us in relation to each other as human beings and also suggests a relationship of responsibility between the state and its institutions and the individual.”[6] Vulnerability theory critiques the contemporary understanding of “the legal subject,” which is built on an ideology that values liberty over equality and manipulates contractual concepts such as choice and consent to justify exploitation and structural inequality.[7] That inequality has distorted and constrained the conception of the legal subject into a narrow and limited autonomous subject that is at the center of the analysis that law uses to organize society.[8] Human vulnerability theory calls for enriching the legal subject by placing it in social context, and engaging with its complex and dynamic characteristics. The paper is divided into five Parts. Part I provides an overview of human vulnerability theory. Part II presents a vulnerability perspective on liberalism and neoliberalism, two theories that underlie the current global climate regime. Part III examines the concept of vulnerability in the climate discourse, while Part IV applies human vulnerability theory to the global climate regime. The final part states the conclusions. [1] Anna Grear, Vulnerability, Advanced Global Capitalism and co-Symptomatic Injustice: Locating the Vulnerable Subject, in Vulnerability: Reflections on a New Ethical Paradigm for Law and Politics 41, 41 (Martha Alberston Fineman & Anna Grear eds., 2013). [2] David Hunter, James Salzman & Durwood Zaelke, International Environmental Law & Policy 3rd ed. 631. Foundation Press, NY (2007). [3] Climate Change and Indigenous Peoples, United Nations Permanent Forum on Indigenous Issues, http://www.un.org/en/events/indigenousday/pdf/Backgrounder_ClimateChange_FINAL.pdf [http://perma.cc/7G3H-M9MP]. [4] Berhanu F. Alemaw & Timothy Simalenga, Climate Change Impacts and Adaptation in Rainfed Farming Systems: A Modeling Framework for Scaling-Out Climate Smart Agriculture in Sub-Saharan Africa, 4 Am. J. of Climate Change 313 (2015). [5] See Klaus Bosselmann, The Rule of Law Grounded in Earth (2013), p.5. [6] Vulnerability and the Human Condition, Emory University, http://web.gs.emory.edu/vulnerability/index.html [http://perma.cc/D363-SFCR] [hereinafter Vulnerability Index]. [7] Definitions of Vulnerability and the Human Condition Initiative, Emory University, http://web.gs.emory.edu/vulnerability/about/definitions.html [http://perma.cc/D363-SFCR]. [8] See Martha Albertson Fineman, The Autonomy Myth, The New Press (2004). In this book, Fineman argues that popular ideology in the United States (and adopted in other common law based legal systems) has become fixated on the myth that citizens are and should be autonomous. However, the fact is that dependency is unavoidable in any society and human beings are more or less dependent on others at all stages in the human life-cycle. I extend the notion of dependency to our dependence on the environment and the resources it provides for our subsistence on Earth throughout our lives.